Entomopathogenic fungi on Hemiberlesia pitysophila. - Chengqun Lv (PLoS ONE, 2011)
Hemiberlesia pitysophila Takagi is an extremely harmful exotic insect in forest to Pinus species, including Pinus massoniana. Using both morphological taxonomy and molecular phylogenetics, we identified 15 strains of entomogenous fungi, which belong to 9 genera with high diversities. Surprisingly, we found that five strains that were classified as species of Pestalotiopsis, which has been considered plant pathogens and endophytes, were the dominant entomopathogenic fungus of H. pitysophila. Molecular phylogenetic tree established by analyzing sequences of ribosomal DNA internal transcribed spacer showed that entomopathogenic Pestalotiopsis spp. were similar to plant Pestalotiopsis, but not to other pathogens and endophytes of its host plant P. massoniana. We were the first to isolate entomopathogenic Pestalotiopsis spp. from H. pitysophila. Our findings suggest a potential and promising method of H. pitysophila bio-control.